2016
DOI: 10.1161/jaha.116.003248
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Vascular Mechanics Serve as Biomarkers of Cognitive Dysfunction in Aortic‐Banded Miniature Swine That Can Be Treated With an Exercise Intervention

Abstract: BackgroundCognitive impairment in the setting of heart failure with preserved ejection fraction remains poorly understood. Using aortic‐banded miniature swine displaying pathological features of human heart failure with preserved ejection fraction, we tested the hypothesis that increased carotid artery stiffness and altered carotid blood flow control are associated with impaired memory independent of decreased cardiac output. Furthermore, we hypothesized that chronic exercise prevents carotid artery vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 60 publications
(82 reference statements)
6
33
1
2
Order By: Relevance
“…Given that EF and cardiac output remain normal under resting conditions, HFpEF‐induced vascular dementia may occur independently of resting cardiac systolic dysfunction (ie, decreased pumping capacity of the heart at rest). In a translational large animal model that displays similar cardiac features as human HFpEF, we demonstrated that heart failure–induced deficits in spatial memory in male pigs coincided with increased total peripheral resistance and carotid artery vascular resistance, independent of resting cardiac systolic impairment . These data suggest that cerebrovascular dysfunction may contribute to indexes of vascular dementia in this experimental model of heart failure, and support the notion that HFpEF reflects a total‐body disease affecting the peripheral vasculature and the brain .…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Given that EF and cardiac output remain normal under resting conditions, HFpEF‐induced vascular dementia may occur independently of resting cardiac systolic dysfunction (ie, decreased pumping capacity of the heart at rest). In a translational large animal model that displays similar cardiac features as human HFpEF, we demonstrated that heart failure–induced deficits in spatial memory in male pigs coincided with increased total peripheral resistance and carotid artery vascular resistance, independent of resting cardiac systolic impairment . These data suggest that cerebrovascular dysfunction may contribute to indexes of vascular dementia in this experimental model of heart failure, and support the notion that HFpEF reflects a total‐body disease affecting the peripheral vasculature and the brain .…”
supporting
confidence: 73%
“…Heart failure was induced with AB over a period of 24 weeks, as previously reported by our laboratory, in AB and AB‐OVX miniature swine at 8 months of age. The AB was placed around the ascending aorta, and a systolic transstenotic gradient of ≈70 mm Hg was achieved (73±3 and 72±3 mm Hg for AB and AB‐OVX, respectively; P =0.83).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations